On Michel Foucault: Power/Knowledge, Discourse, and Subjectivity - Poorghorban, Younes (OKARA: Jurnal Bahasa dan Sastra, 2023)
The indubitable significance of Michel Foucault within the realm of modern humanities cannot be overstated. His far-reaching influence across various fields of study has proven to be of paramount importance. The present study is intended to bring into focus the most consequential critical concepts of Michel Foucault. While certain scholars have previously endeavoured to depict and reconceptualise Foucault's principal notions, many of them have tended to complicate the matter by problematising his understanding of these concepts. The most significant concepts include Discourse, Power, Knowledge, and Subjectivity. The nature and function of discourses in shaping knowledge and the relationship between knowledge and power have been subject to investigation. Additionally, this study sheds light on the manner in which subjects are shaped in the duality of power and resistance. The primary objective of this study is to offer a lucid definition of these terms and their interrelatedness.